ShangRing versus Mogen clamp for early infant male circumcision in eastern sub-Saharan Africa: a multicentre, non-inferiority, adaptive, randomised controlled trial. Issue 10 (October 2022) - Basourakos, Spyridon P; Nang, Quincy G; Ballman, Karla V; Al Awamlh, Omar Al Hussein; Punjani, Nahid; Ho, Kaylee; Barone, Mark A; Awori, Quentin D; Ouma, Daniel; Oketch, Jairus; Christensen, Alice E; Hellar, Augustino; et al.
Summary: Background: Use of medical devices represents a unique opportunity to facilitate scale-up of early infant male circumcision (EIMC) across sub-Saharan Africa. The ShangRing, a circumcision device prequalified by WHO, is approved for use in adults and adolescents and requires topical anaesthesia only. We aimed to investigate the safety and efficacy of the ShangRing versus the Mogen clamp for EIMC in infants across eastern sub-Saharan Africa. Methods: In this multicentre, non-inferiority, open-label, randomised controlled trial, we enrolled healthy male infants (aged <60 days), with a gestational age of at least 37 weeks and a birthweight of at least 2·5 kg, from 11 community and referral centres in Kenya, Tanzania, and Uganda. Infants were randomly assigned (1:1) by a computer-generated text message service to undergo EIMC by either the ShangRing or the Mogen clamp. The primary endpoint was safety, defined as the number and severity of adverse events (AEs), analysed in the intention-to-treat population (all infants who underwent an EIMC procedure) with a non-inferiority margin of 2% for the difference in moderate and severe AEs. This trial is registered with Clinical. Trials.gov, NCT03338699, and is complete. Findings: Between Sept 17, 2018, and Dec 20, 2019, a total of 1420 infants were assessed for eligibility, of whom 1378 (97·0%) were enrolled. 689 (50·0%) infants were randomly assigned to undergo EIMC by ShangRing and 689 (50·0%) by Mogen clamp. 43 (6·2%) adverse events were observed in the ShangRing group and 61 (8·9%) in the Mogen clamp group (p=0·078). The most common treatment-related AE was intraoperative pain (Neonatal Infant Pain Scale score ≥5), with 19 (2·8%) events in the ShangRing and 23 (3·3%) in the Mogel clamp group. Rates of moderate and severe AEs were similar between both groups (29 [4·2%] in the ShangRing group vs 30 [4·4%] in the Mogen clamp group; difference –0·1%; one-sided 95% CI upper limit of 1·7%; p=0·89). No treatment-related deaths were reported. Interpretation: Use of the ShangRing device for EIMC showed safety, achieved high caregiver satisfaction, and did not differ from the Mogen clamp in other key measures. The ShangRing could be used by health systems and international organisations to further scale up EIMC across sub-Saharan Africa. Funding: Bill & Melinda Gates Foundation.